Improvement of a low-level mesurement system used at LNHB. (March 2016) - Ferreux, Laurent; Bouchard, Jacques
Abstract: In this new approach, the active shielding of a low level spectrometer is monitored by an extendable dead time used as an "extendable GATE" signal. This concept is directly inspired from the live-timed anti-coincidence system implemented at LNE-LNHB (MTR2 modules). This allows a significant reduction in the cost and complexity of the system since several electronic modules are replaced by only one module dedicated specifically to this type of experiment. Settings of this new approach are detailed and results are discussed. Highlights: Low-level gamma spectrometry system for environmental monitoring. System based on the extendible dead-time and live-time. Improvement by a factor of 2 on the integral background count-rate. Improvement by a factor of 5 on the 511 keV peak.